RARE EARTH ELEMENT AND YTTRIUM VARIABILITY IN SOUTH EAST QUEENSLAND WATERWAYS - Lawrence M.G.; Greig A.; Collerson K.D.; Kamber B.S. (My University, 2006)
We present data for the rare earth elements and yttrium (REY) in the National Research Council of Canada natural river water reference material SLRS-4 and 19 natural river waters from small catchments in South-East Queensland, Australia, by a direct ICP-MS method. The 0.22 μm filtered river water samples show a large degree of variability in both the REY concentration, e.g., La varies from 13 to 1157 ppt, and shape of the alluvial-sediment-normalised REY patterns with different samples displaying light, middle or heavy rare earth enrichment. In addition, a spatial study was undertaken along the freshwater section of Beerburrum Creek, which demonstrates that ~75% of the total REYs in this waterway are removed prior to estuarine mixing without evidence of fractionation.
Keywords: FRACTIONATION; ICP-MS; QUEENSLAND; RARE EARTH ELEMENTS; RIVERS; SLRS-4; YTTRIUM